(untitled) (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2024)
Virgil’s Dido is here reinterpreted in an unconventional key compared to the stereo-type of the mad love that has habitually enveloped her fame. She is discussed in the light of a rep-resentation so far little appreciated by critics: that of an avid fan of the classic epic. It is this mania for heroic myths that leads her to beg Aeneas to tell her about his adventurous life. The story of the veteran of the Trojan War is the spark that ignites the already latent erotic passion in her. As we try to demonstrate at the end of the essay, this archetype could be the basis of Dante’s construction of the figure of Francesca, counted among that group of strong readers of stories of heroes who transfer into real life what they have learned from the products of literary imagination.